2022
DOI: 10.1186/s13018-022-02948-2
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of chronic Achilles tendon rupture results in improved gait biomechanics

Abstract: Background Chronic Achilles tendon rupture is associated with persistent weakness at push-off with the affected foot and poor balance, resulting in significant alterations to normal gait. Surgical repair is the most common treatment for improving gait in patients with a Chronic Achilles tendon rupture, but, to date, the outcomes have not been quantified in the literature. Methods A total of 23 patients with a Chronic Achilles tendon rupture (mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…In reference to the results obtained by other authors, who assessed the behavior of the biomechanical gait parameters over a period of 6 to 12 months, as well as in a longer period of time after AT surgery [ 12 , 13 , 14 , 21 , 27 , 28 , 29 ], our study showed a significant improvement in the twentieth week after surgical suturing of Achilles tendon using an open method (SSATOM) in most of the analyzed values of 3D gait parameters. However, the authors of the current study did not achieve the restoration of all gait parameters in patients after SSATOM, which would be similar to the non-operated side and the results of the control group.…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…In reference to the results obtained by other authors, who assessed the behavior of the biomechanical gait parameters over a period of 6 to 12 months, as well as in a longer period of time after AT surgery [ 12 , 13 , 14 , 21 , 27 , 28 , 29 ], our study showed a significant improvement in the twentieth week after surgical suturing of Achilles tendon using an open method (SSATOM) in most of the analyzed values of 3D gait parameters. However, the authors of the current study did not achieve the restoration of all gait parameters in patients after SSATOM, which would be similar to the non-operated side and the results of the control group.…”
Section: Discussionmentioning
confidence: 94%
“…The literature analysis indicates that some of the authors presented a biomechanical assessment of gait in patients treated conservatively [ 22 , 26 , 40 , 41 , 42 ] and surgically [ 21 , 27 , 43 ] after AT rupture. Moreover, studies indicate that the authors used various methods and surgical techniques [ 44 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations